A novel view of the destruction of Pompeii during the 79 CE eruption of Vesuvius (Italy): syn-eruptive earthquakes as an additional cause of building collapse and deaths - Sparice, Domenico; Amoretti, Valeria; Galadini, Fabrizio; Di Vito, Mauro A.; Terracciano, Antonella; Scarpati, Giuseppe; Zuchtriegel, Gabriel (Frontiers in Earth Science, 2024)
The ancient city of Pompeii, destroyed by the 79 CE Plinian eruption of Vesuvius, is one of the most famous archaeological sites worldwide and an open-air laboratory for many disciplines. The destruction of Pompeii has so far been reconstructed in terms of a succession of volcanic phenomena and related effects, identified as the accumulation of pumice lapilli on roofs and dynamic pressure exerted by pyroclastic currents on buildings, and neglecting the potential effects of the syn-eruptive seismicity, the occurrence of which is beautifully described by an erudite eyewitness to the catastrophe, Pliny the Younger. During a recent excavation in the Insula dei Casti Amanti, in the central part of Pompeii, the peculiar evidence of building collapses, that overwhelmed two individuals, has been uncovered. The multidisciplinary investigation, involving archaeology, volcanology, and anthropology, gathered information on the construction technique of the masonry structures, the volcanological stratigraphy, the traumatic pattern of bone fractures of the skeletons, along with the detection of the wall displacements, that led to archaeoseismological considerations. The merging of the data has highlighted the need of an updated perspective in the assessment of the damage at Pompeii during the 79 CE eruption, by considering the syn-eruptive seismicity as a factor contributing to the destruction of the city and death of the inhabitants. By comparing the attitude and characteristics of different types of damage, and after ruling out any other possible damaging event, our conclusions point to the occurrence of syn-eruptive earthquake-induced failures of masonry structures. The structural collapses, based on our stratigraphic and volcanological data, are chronologically consistent with the beginning of the caldera-forming phase of the eruption which was accompanied by strong seismic shocks. The crush injuries of the skeletons of the two individuals are consistent with severe compression traumas and analogous to those shown by individuals involved in modern earthquakes testifying that, apart from other volcanic phenomena, the effects of syn-eruptive seismicity may be relevant. These outcomes lay the foundation for a more extensive study concerning the assessment of the contribution of the syn-eruptive seismic destruction at Pompeii and open new perspectives for volcanological, archaeoseismological and paleopathological studies.